Curcumin and derivatives function through protein phosphatase 2A and presenilin orthologues in Dictyostelium discoideum - Marco Cocorocchio; Amy J. Baldwin; Balint Stewart; Lou Kim; Adrian J. Harwood; Christopher R. L. Thompson; Paul L. R. Andrews; Robin S. B. Williams (The Company of Biologists, 2018)
Natural compounds often have complex molecular structures and unknown molecular targets. These characteristics make them difficult to analyse using a classical pharmacological approach. Curcumin, the main curcuminoid of turmeric, is a complex molecule possessing wide-ranging biological activities, cellular mechanisms and roles in potential therapeutic treatment, including Alzheimer's disease and cancer. Here, we investigate the physiological effects and molecular targets of curcumin in Dictyostelium discoideum. We show that curcumin exerts acute effects on cell behaviour, reduces cell growth and slows multicellular development. We employed a range of structurally related compounds to show the distinct role of different structural groups in curcumin's effects on cell behaviour, growth and development, highlighting active moieties in cell function, and showing that these cellular effects are unrelated to the well-known antioxidant activity of curcumin. Molecular mechanisms underlying the effect of curcumin and one synthetic analogue (EF24) were then investigated to identify a curcumin-resistant mutant lacking the protein phosphatase 2A regulatory subunit (PsrA) and an EF24-resistant mutant lacking the presenilin 1 orthologue (PsenB). Using in silico docking analysis, we then showed that curcumin might function through direct binding to a key regulatory region of PsrA. These findings reveal novel cellular and molecular mechanisms for the function of curcumin and related compounds.